Implementasi The Onion Router (Tor) Berbasis Virtual Private Network (VPN) pada Raspberry Pi - Kenny Kenny; Kartika Gunadi; Leo Willyanto Santoso (Jurnal Infra, 2017)
Internet that we use everyday is not fully secured from hackers that want to do cybercrime. Today, the Internet has become part of our daily lives as one of the means of communication in business as well as for individuals. But behind that there are many holes weakness of the system on the internet that can be exploited by the cracker for not good purposes, such as mail bombs, randomization of home page, data theft, password or credit card number. Most of security that people used in general is only the basic security system.This application is created using the programming language Python and html. The interface of app using Bottle Python Web Framework that can be accessed via IP Gateway. This is made in Raspberry Pi which is equipped with 16x2 LCD.The result of this development is we are able to use VPN and Tor simultaneously so that surfing / browsing on the internet becomes more secure and can access some websites that have been blocked like reddit forum. With this application cyber hackers will have trouble in doing tracking.